Natural Gas New Perspectives and Future Developments - Takht Ravanchi, Maryam (IntechOpen, 2022)
Natural gas as a non-renewable hydrocarbon is used as an energy source for cooking, heating, vehicle fuel, and electricity generation. It is also used as a chemical feedstock in the manufacturing of plastics and organic chemicals. This book brings together new perspectives and future developments in natural gas. Chapters address such topics as adsorbed natural gas, fermentation processes for producing value-added products from natural gas, processes for separating C3+ hydrocarbon from natural gas, natural gas dehydration, and much more.